Der Holocaust und die Katechismusdebatte – ein Exemplum politischen Urteilens auf dem Prüfstand - Hähnlein, Astrid (HannahArendt.net, 2025)
Drawing on Hannah Arendt's theory of political judgment, this article examines the Holocaust as an exemplum of political reasoning and interrogates the implications of its contested status within the so-called "Catechism Debate" (Katechismusdebatte) — the ongoing second Historikerstreit.For Arendt, reflective judgment operates not through the subsumption of particulars under pre-given universals, but by thinking within and through the concrete case itself — allowing the particular example to yield normative orientation without being dissolved into abstraction. Exemplary figures, literary works, and historical events — Achilles, the Mayflower, Adolf Eichmann — function as normative benchmarks that simultaneously enable individual judgment and constitute the shared referential ground of a sensus communis. The Holocaust, long accorded the status of an uncontested negative exemplum, serves as precisely such a civilizational touchstone: a radical rupture that, as both Arendt and Adorno recognized, places irreducible demands on subsequent moral and political thought.This singular standing, however, is increasingly challenged by postcolonial scholarship. A. Dirk Moses's charge of a "German catechism" and Michael Rothberg's advocacy of "multidirectional memory" question whether the emphasis on Holocaust uniqueness has structurally marginalized colonial and imperial atrocities. The article argues that while such critical reassessment constitutes a legitimate exercise in political judgment, the erosion of a shared exemplary reference point carries real consequences for the communicability of moral and political verdicts — a concern Jürgen Habermas has articulated with particular urgency.In conclusion, the article turns to Arendt's distinction between genius and taste to suggest that the legitimacy of comparative Holocaust references ultimately depends less on scholarly authority than on the intersubjective judgment of a community of engaged readers and citizens.